Fault Type Determination on Distribution Networks Lines within Functions of Microprocessor Current Protections - F. A. Romaniuk; A. A, Tishechkin; E. V. Buloichyk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The main disadvantage of the existing microprocessor current protections of distribution networks lines of 6–35 kV is a comparatively short instantaneous trip zone of the first step and insufficient sensitivity of the third step in many cases of asymmetrical short-circuits. The noted disadvantages can be eliminated by changing the current settings of steps in concordance with detected two-phase fault modes. Asymmetrical fault mode detection can be carried out through checking of a relative asymmetry of currents in the line phases. The paper presents a comparative estimation of techniques for asymmetrical fault determination on distribution networks lines and contains an analysis of the results pertaining to the investigations on application of aforementioned techniques in the line microprocessor current protection algorithms. The investigations have been carried out while using a computing experiment method. The computing experiment has confirmed efficiency and high sensitivity of the proposed method, which makes it possible to clearly establish solid two-phase fault on both the controlled and contiguous lines. Using the computing experiment method the transient resistance influence in the fault location on the fault type determination accuracy has been also investigated.